12th Gawad Cultural Center of the Philippines (CCP) para sa alternatibong pelikula at video - Co, Ferdinand (Animo Repository, 1999)
Two DLSU works on documentary were cited as honorable mention in the 12th Gawad Cultural Center of the Philippines (CCP) para sa Alternatibong Pelikula at Video. One was Si Mam, Si Sir by Ferdinand Co, Melissa Lopez and Reginald Ibarra. The other documentary, Sabong, Alagad ni Kristo was made by Rosel Brocal and Geraldine Trillana.